2015
DOI: 10.1007/s10072-015-2218-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory axons excitability changes in carpal tunnel syndrome after neural mobilization

Abstract: Increased mechanosensitivity of the median nerve in carpal tunnel syndrome (CTS) has been demonstrated during upper limb tension test 1 (ULTT1) when the nerve is passively elongated. However, the neurophysiological changes of the sensory axons during stressing activities are unknown. The aim of present study was to verify possible changes in the excitability of median nerve afferent axons following nerve stress in elongation, in subjects with and without CTS. Eight CTS hands and eight controls were selected. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Prior studies have demonstrated that most clinical anatomic characteristics of the median nerve stiffness in patients with carpal tunnel syndrome showed a flat median nerve at the hook of the hamate bone (the thickest flexor retinaculum) and a dilated median nerve at the proximal pisiform bone. The carpal tunnel inlet and boundary of the flexor retinaculum are located at the pisiform bone near the hook of the hamate bone, which is where the front median nerve wall of most patients with carpal tunnel syndrome was relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that most clinical anatomic characteristics of the median nerve stiffness in patients with carpal tunnel syndrome showed a flat median nerve at the hook of the hamate bone (the thickest flexor retinaculum) and a dilated median nerve at the proximal pisiform bone. The carpal tunnel inlet and boundary of the flexor retinaculum are located at the pisiform bone near the hook of the hamate bone, which is where the front median nerve wall of most patients with carpal tunnel syndrome was relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…The mobilization was shown to redistribute the sodium ion channels of sensory axons (25), increase neural growth factor and myelin protein zero in injured nerves (38,39). Overall, the therapeutic effects of the nerve mobilization could be accounted for by reduction of physical stress through the movements of the nerves (17,18) and intraneural fluid dispersion (19,20), normalization of sensory axons excitability (25), and promotion of nerve regeneration by stimulating expression of neural growth factor and myelin protein zero (38,39).…”
Section: N Discussionmentioning
confidence: 99%
“…Overall, the therapeutic effects of the nerve mobilization could be accounted for by reduction of physical stress through the movements of the nerves (17,18) and intraneural fluid dispersion (19,20), normalization of sensory axons excitability (25), and promotion of nerve regeneration by stimulating expression of neural growth factor and myelin protein zero (38,39). As a pilot study, the methodology had several limitations such as sample size, subjects' homogeneity and the length of the follow-up period.…”
Section: N Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial onset sensory and motor neuronopathy (FOSMN) is a recently defined slowly progressive motor neuron disorder [145]. Brachial plexus injury (BPI) causes functional changes in the brain, but the structural changes resulting from BPI remain unknown [146]. Neuromyotoxicity due to therapy with hydroxychloroquine has been reported in a case [147].…”
Section: Neuromuscular Disordersmentioning
confidence: 99%